The Influence of Personality, Entrepreneurship Education and Family Environment on Students' Entrepreneurial Interest in Surabaya - Ilham Naufal, Muhammad; Arumsari, Devinta; Budiman , Arief (Jurnal Mebis, 2024)
This research explores the influence of personality, entrepreneurial education, and family environment on students' entrepreneurial interest in Surabaya. This study uses quantitative methods with a survey involving students from various universities in Surabaya. Analysis was carried out using PLS (Partial Least Square) to see the relationship between the independent variables (personality, entrepreneurship education, and family environment) and the dependent variable (interest in entrepreneurship). The research results show that personality has a significant influence on interest in entrepreneurship. Apart from that, entrepreneurship education also has a positive effect on interest in entrepreneurship. The family environment also has an important role in increasing interest in entrepreneurship. Good family support significantly increases interest in entrepreneurship among Surabaya students.